PENGARUH DESAIN KERJA DAN MANAJEMEN TEKNOLOGI INFORMASI TERHADAP MUTU PELAYANAN GURU SMK NEGERI DI WILAYAH JAKARTA UTARA - Sopiah Sopiah (Universitas Negeri Jakarta, 2017)
This study aims to determine the effect of job design and management information technologi on service quality State Senior High School in Nort Jakarta.The method used ini this research is survey method with path analysis techniques. This study used a population of teachers State Senior High School in Nort Jakarta much as 150 teachers. Sampling techniques in this study is proportional random sampling methode.Based on the results of the study can be summarized as follows: Firstly, there is the effect of job design on service quality; Secondly, there is the effect of management information technology on service quality; Third, there is the effect of job design on management information technology.